Parametric study of twin tunnel under seismic loads for Cairo Metro Line No. 4. Issue 1 (1st January 2021) - Kamal, Heba; Hussein, Manar; Akl, Adel
ABSTRACT: The damage of tunnel induced by intense earthquake is obviously important. Thus, more attention has been paid to the tunnel destruction induced by earthquake. So far, there are few studies conducted on the influence of earthquake dynamic loads on horizontal twin tunnels. In this research, a systematic analysis of horizontal twin tunnels of Cairo Metro Line No. 4 was performed using finite element model by the commercial software PLAXIS 2D and under static and earthquake dynamic loads using the Dahsour Earthquake 1992 time real history. Both static and dynamic analyses in this research have taken into account the effect of the soil structure interaction on the static and dynamic performance of horizontal twin tunnels. Also, a parametric study had been performed on the horizontal twin tunnels of Cairo Metro Line No. 4 under different parameters, which included the tunnel's depth ( d ), the distance between twin tunnels ( S ), and the surrounding soil stiffness ( E ). Results showed that both static and dynamic analysis are expected to be governed by soil structure interaction. Also, the studied parameters are very important in tunnel design under static and dynamic loads, especially the distance between twin tunnel, where these types of twin tunnels were excavated by TBM machine.